A longitudinal investigation of sports-related risk factors for disordered eating in aesthetic sports - Krentz, E. M.; Warschburger, P. (Scandinavian Journal of Medicine & Science in Sports, 2013)
Previous studies have indicated a higher risk of disordered eating in certain types of elite sports such as aesthetic sports (e.g., rhythmical gymnastics, figure skating). But even though some studies on risk factors for disordered eating in sports exist, most research on this topic is based on cross-sectional data with limitations on causal inferences. We examined sports-related risk factors for disordered eating in a 1-year longitudinal study with two assessment points. The participants were 65 adolescent athletes from aesthetic sports (mean age 14.0 ± 2.2 years) who completed measures of disordered eating, social pressure from the sports environment, sports-related body dissatisfaction, desire to be leaner to improve sports performance, and emotional distress resulting from missed exercise sessions. All variables were relatively stable in the mean. Individual changes in the desire to be leaner to improve sports performance were associated with individual changes in disordered eating. Furthermore, a cross-lagged partial correlation analysis showed that the desire to be leaner to improve sports performance was predictive of disordered eating and not vice versa. The results of our study indicate that athletes are more at risk for disordered eating if they believe it is possible to enhance their sports performance through weight regulation.